The new achievements in ultrasonic processing of milk and dairy products. Issue 1 (March 2022) - Mahmoud, Mustafa Z.; Davidson, Rob; Abdelbasset, Walid Kamal; Fagiry, Moram A.
Abstract: The effects of ultrasonic wave vibration, streaming, and cavitation have expanded the usage of ultrasound in milk and dairy industries. This review will look at the latest achievements in ultrasonic processing of milk and dairy products. Given the significant advances in the utilization of ultrasonic processing in milk and dairy products since the millennium, studies have been incorporated into outcome analysis. While ultrasonic crystallization, creaming, and fractionation are advancing faster, interesting achievements in dairy product functionality have emerged. Non-food contact transducers are scalable and better suited for industrial processes. In conclusion, large-scale processing equipment, alone or in combination with other technologies, will help expand ongoing microbial reduction processes.